EVALUASI DAMPAK KEBIJAKAN PENGELOLAAN WILAYAH PESISIR DAN LAUT DI KABUPATEN REMBANG - Roziqin, Ali; Kismartini, Kismartini (Journal of Public Policy and Management Review, 2016)
Rembang is an area located on the north coast of Central Java. The potential of coastal and marine areas in Rembang considerable, but so far there is damage to the environment and utilization is not optimal. Based on this background problem that arises is How pengeolaan policy impact coastal and marine areas in Rembang? How to constraints in the policy management of coastal areas and the sea in Rembang. The purpose of this study was to evaluate the impact of the policy management of coastal and marine areas in Rembang. In addition to knowing the constraints in the policy management of coastal and marine areas in Rembang. Based on the research that the policy management of coastal and marine areas in Rembang having an impact on people's lives, but not optimal and equitable perceived by the public. Not optimal goal and the impact felt by the target group due to some constraints in the implementation of policies such as kuragnya coordination and collaboration among relevant agencies, lack of understanding of personnel, lack of dissemination of relevant SKPD or of society such as the low level of education of coastal communities, the lack of awareness and the community's participation. Under these conditions, the authors provide suggestions for the government to undertake intensive socialization, improved understanding of the content of the policy apparatus, increasing the level of education of coastal communities. Then for the community to increase participation and to change the mindset that tends to badly in the costal management and marine.